Novel bivalent transition metal complexes based on a 2-amino-3-hydroxypyridine Schiff base ligand: synthesis elucidation, antimicrobial evaluation, antioxidant and molecular docking studies - A. Z. El-Sonbati; A. A. El-Bindary; N. M. Mansour; M. M. El-Zahed (BMC Chemistry)
Abstract Cu(II), Co(II), Ni(II), Mn(II), and UO2(II) complexes have been prepared and studied using a Schiff base generated from 2,4-dihydroxybenzaldehyde and 2-amino-3-hydroxypyridine. Various spectroscopic methods have inferred the complexes' shape and bonding type. The Schiff base and its metal complexes were examined for antibacterial activity against bacteria including Pseudomonas aeruginosa, Bacillus cereus, Escherichia coli, and Staphylococcus aureus, as well as fungi such as Fusarium oxysporum, Aspergillus niger, and Candida albicans. The in vitro antimicrobial assay was conducted using the agar well diffusion method, minimum inhibition concentration (MIC), and minimum microbicidal concentration (MMC) tests. All prepared compounds demonstrated effective inhibition potential against the selected harmful fungi compared to their antibacterial activity. The antioxidant assay utilizing the DPPH method indicated that Mn(II), Cu(II), Co(II), and Ni(II) complexes were the most active compounds, showing DPPH radical scavenging activities of 76.2, 68.4, 65.3, and 60.1% inhibition, respectively. This study also evaluated the molecular docking performance and interaction mechanisms of the ligand and its metal complexes against three fungal targets: C. albicans (PDB ID 5V5Z), A. niger (PDB ID 3PL3), and F. oxysporum (PDB ID 1FN8). Docking scores (S), interaction energies, and refined RMSD values were calculated. Results revealed that complex (3) exhibited the strongest binding affinity against C. albicans (S = −9.28784), while complex (5) showed notable interactions with F. oxysporum. Key interactions included hydrogen bonds, π–H, and π-cation interactions, with energies reaching as low as −4.4 kcal/mol. These findings highlight the potential of metal-based complexes as antifungal agents. The results demonstrated that the Schiff base and its metal complexes possess promising antimicrobial activity, which may be beneficial for pharmaceutical and industrial applications.